1993
DOI: 10.1080/01635589309514265
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumor Promoter‐induced hydrogen peroxide formationin vitroandin vivoby genistein

Abstract: Here we report that genistein, a soybean isoflavone, strongly inhibits tumor promoter-induced H2O2 formation both in vivo and in vitro. Genistein suppressed H2O2 production by 12-O-tetradecanoylphorbol-13-acetate- (TPA) stimulated human polymorphonuclear leukocytes (PMNs) and HL-60 cells in a dose-dependent manner over the concentration range 1-150 microM. Human PMNs were more sensitive to the inhibitory effect of genistein than HL-60 cells (50% inhibitory concentration 14.8 and 30.2 microM, respectively). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
157
0
8

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(168 citation statements)
references
References 28 publications
3
157
0
8
Order By: Relevance
“…The phytoestrogen genistein has been shown to have antitumor promotional effects in vivo and in vitro attributed to the inhibition of the production of oxidative radical species (34)(35)(36). Because both genistein and estradiol, but not the nonsteroidal oleanolic acid or protocatechuic acid, were reported to protect DNA from the induction of 8-hydroxy-deoxyguanosine by UVC radiation in vitro (36), an ER-dependent mechanism was implicated. In support are very recent studies in the rat reporting that the relevant DNA repair enzyme, 8-oxoguanine glycosylase, was significantly decreased in neuronal tissue after ovariectomy (37).…”
Section: Discussionmentioning
confidence: 99%
“…The phytoestrogen genistein has been shown to have antitumor promotional effects in vivo and in vitro attributed to the inhibition of the production of oxidative radical species (34)(35)(36). Because both genistein and estradiol, but not the nonsteroidal oleanolic acid or protocatechuic acid, were reported to protect DNA from the induction of 8-hydroxy-deoxyguanosine by UVC radiation in vitro (36), an ER-dependent mechanism was implicated. In support are very recent studies in the rat reporting that the relevant DNA repair enzyme, 8-oxoguanine glycosylase, was significantly decreased in neuronal tissue after ovariectomy (37).…”
Section: Discussionmentioning
confidence: 99%
“…Genistein, a natural isoflavonoid found in soybean products, has been proposed to be associated with a lower rate of breast cancer in Asian women (Fotsis et al, 1995;Lamartiniere et al, 1995) and is believed to be a chemopreventive agent (Lamartiniere et al, 1995). Genistein has been known to compete with estradiol for estrogen receptor binding as weak estrogen (Bradlow and Sepkovic, 2002), to regulate signal transduction as inhibitor of protein tyrosine kinases (Akiyama et al, 1987), and to inhibit cellular oxidative stress (Wei et al, 1993) and angiogenesis (Fotsis et al, 1995(Fotsis et al, , 1997. The in vitro and in vivo experimental studies from our laboratory and other investigators have shown that genistein can inhibit the growth of various cancer cell lines through cell cycle arrest (G2/M) and downregulation of cyclin B1 and cdc25C, induce apoptosis through upregulation of p21 WAFI and Bax expression and activation of CPP32, and inhibit invasion of different tumor cells in vitro with downregulation of MMP-9 and upregulation of TIMP-1 (Constantinou et al, 1990;Spinozzi et al, 1994;Davis et al, 1998;Lian et al, 1998;Shao et al, 1998;Alhasan et al, 1999;Li et al, 1999a,b;Santibanez et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The isoflavone biochanin A (5,7-dihydroxy-4 -methoxyisoflavone) (50 M) was chosen as the substrate since it is a poor inhibitor of protein tyrosine kinases and myeloperoxidase activity [15]. Cells were suspended in phosphate-buffered saline and incubated at 37 • C. An oxidative burst of HOCl was created by adding PMA (10 M).…”
Section: Cell Culturementioning
confidence: 99%
“…1), has been shown to have several biological and biochemical effects. These range from being an inhibitor of protein tyrosine phosphorylation [12] and tumor necrosis factor alpha activation [13], as an agonist and antagonist of the estrogen receptors, ␣ and ␤ [14], and as an anti-oxidant [15].…”
Section: Introductionmentioning
confidence: 99%